Risk Perception, Self-Control, Self-Regulation, Abnormalities on Risky Driving Tendency with Defensive Driving as Mediator - Pradjojowaty, Ika Setyorini (Interdisciplinary Social Studies, 2023)
Background: Reckless bus drivers are still roaming on the highway. They usually make reasons like they are chased by deposits or so as not to be sleepy so they do the action. Even though when riding a bus, the driver certainly carries passengers and must be responsible for their safety. Aim: To provide an overview or model of intervention in dealing with risky driving behavior that is influenced by perceptions of safety risk, self control, self regulation, normlessness as factors behind risky driving behavior in Intercity Interprovincial Bus drivers, which is mediated by defensive driving behavior. Method: This study used a mix method, namely the calculation of questionnaire results using SmartPLS to see the model and the discussion of research uses more qualitative. The data used are secondary data, and primary data collected through filling out a closed questionnaire with a Likert scale of 1-5. The total respondents sampled in this study ranged from 50 bus drivers from PO Santoso and PO Handoyo at Bekasi City terminal, so the total number of respondents is around 100 people. Findings: There is a correlation or influence between risk perception, self control, n ormlessness and self regulation, significantly on risky driving behavior with defensive driving as a mediator. Risk perception had a significant influence on risky driving behavior. On the other hand, normlessness is very influential significantly because there is defensive driving as a mediator so that it is very effective if there is no defensive driver as a mediator.